2018
DOI: 10.1590/0004-282x20180018
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset Pompe disease: what is the prevalence of limb-girdle muscular weakness presentation?

Abstract: Pompe disease is an inherited disease caused by acid alpha-glucosidase (GAA) deficiency. A single center observational study aimed at assessing the prevalence of late-onset Pompe disease in a high-risk Brazilian population, using the dried blood spot test to detect GAA deficiency as a main screening tool. Dried blood spots were collected for GAA activity assay from 24 patients with "unexplained" limb-girdle muscular weakness without vacuolar myopathy in their muscle biopsy. Samples with reduced enzyme activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Although no longer classified as a muscular dystrophy of the autosomal recessive type 2 V (LGMD2V) [8] in the updated nomenclature for LGMD, Pompe disease (MIM# 232300), also known as Glycogen Storage Disease Type II, is a rare metabolic disease with a broad clinical spectrum and overlapping signs and symptoms to recessive LGMDs [9]. The estimated prevalence of Pompe disease varies from 1:40,000 to 1:60,000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no longer classified as a muscular dystrophy of the autosomal recessive type 2 V (LGMD2V) [8] in the updated nomenclature for LGMD, Pompe disease (MIM# 232300), also known as Glycogen Storage Disease Type II, is a rare metabolic disease with a broad clinical spectrum and overlapping signs and symptoms to recessive LGMDs [9]. The estimated prevalence of Pompe disease varies from 1:40,000 to 1:60,000.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the success rate of sequencing of a gene panel for the diagnosis of LGMD R or LOPD has not been reported in the Latin American population. A recent study that looked at enzymatic activity showed a 4.2% yield for Pompe disease [9]; however, no study designed to assess variants in a Latin American population or how Pompe disease is related with other LGMD has been conducted. We investigated the sensitivity and specificity for the detection of variants in a gene panel associated with the most common forms of LGMD R and LOPD in a population with undiagnosed limb-girdle weakness in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…The latter abnormality was detected in one patient by Lorenzoni et al ,39 who searched for LOPD in patients with unclassified limb-girdle muscle weakness (LGMW) without vacuolar myopathy. There is potential for detecting LOPD from a muscle biopsy if at least acid phosphatase activity is increased 39. The authors often observed an increased intermyofibrillar network of glycogen; nevertheless, since the DBS screening was negative, this sign should be accepted as an unspecific change.…”
Section: Discussionmentioning
confidence: 98%
“…Given the need for early diagnosis and treatment, a low threshold for screening for LOPD is crucial in patients with unclassified limb-girdle muscle weakness and/or with asymptomatic hyperCKemia [5,10,15,19,20,23]. In the Polish population, we have performed screening for LOPD in a cohort of patients with limb-girdle muscle weakness and/or persistent hyperCKemia, confirming the diagnosis in 3% of patients.…”
Section: Neuromuscular Symptomsmentioning
confidence: 88%
“…LOPD presents with slowly progressive limb-girdle muscle weakness in 78-95% of patients [15][16][17][18]. Muscle fatigue, exercise intolerance, decreased mobility, axial muscle weakness and myalgia are also frequently reported [1,[19][20][21].…”
Section: Neuromuscular Symptomsmentioning
confidence: 99%